Analisis Biaya Satuan Pendidikan dengan Metode Activity Based Costing - Mursyid, Ali; Hidayat, Ara (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
This research aims to analyze the determination of educational unit costs at MTs Muslimin Bojong Picung by applying the Activity Based Costing (ABC) method. This research is important to evaluate the correspondence between applied and actual costs and find potential cost allocation improvements. This type of research is descriptive with a quantitative approach, using data obtained through interviews, documentation and observation. The data analysis method used is quantitative descriptive analysis to explain the unit costs of education. The research results show that the unit costs produced using the ABC system are higher than the education costs set by the madrasah. This finding indicates the existence of undercosting, namely a situation where the actual costs are lower than the estimates produced by the ABC method. Contributing factors include costs that are not detailed or well identified as well as costs that are not charged to students by the madrasah. This research provides insight into inaccurate cost estimates and recommendations for improvements in education cost management.